Retention of provitamin A carotenoids in high-provitamin A biofortified maize and eggs after various cooking methods - Sowa, Margaret; Goltz, Shellen; Tanumihardjo, Sherry A. (2017)
Biofortification of staple crops to increase the content of provitamin A carotenoids (such as beta-carotene and beta-cryptoxanthin) is a strategy being implemented to increase dietary intake of vitamin A in regions where deficiency presents a widespread problem. Heat and light can cause isomerization and oxidation of carotenoids, potentially reducing the provitamin A activity of foods made with biofortified maize after cooking and processing. Thus, an understanding of the provitamin A retention after cooking is important for assessing the utility and maximizing the efficacy of biofortified foods. Retention of carotenoids in eggs from chickens fed high-beta-cryptoxanthin maize was assessed after frying, boiling, and microwaving. Retention of carotenoids in high-beta-cryptoxanthin maize was assessed in muffins, tortillas, porridge, and fried polenta made from both whole-grain and sifted maize flour. This work demonstrates that provitamin A retention may be influenced by cooking, and processing methods should be taken into consideration when breeding and implementing biofortified maize varieties.